Effect of 2000-meter rowing test on parameters of intestinal integrity in elite rowers during competitive phase - observational study - Dziewiecka, H.; Ostapiuk-Karolczuk, J.; Kasperska, A.; Cichon-Wozniak, J.; Basta, P.; Skarpanska-Stejnborn, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The epithelial wall leakage has been extensively studied in sports disciplines like running and cycling. However, little is known about gut permeability in other disciplines, like rowing, especially after the regular competition performance distance of 2000 m. Therefore, our study aimed to check gut permeability after the 2000-meter rowing test in the annual training cycle. The phenomenon of epithelial wall leakage has been the subject of investigations within athletic domains such as running and cycling. Nevertheless, there exists an insufficiency of understanding regarding gut permeability in alternative disciplines, such as rowing, particularly following the completion of a standard competitive distance of 2000 m. Hence, the principal objective of our study was to assess gut permeability after the completion of a 2000-meter rowing test.